Perbandingan Latihan Rondos Dengan Circle Passing Drill Terhadap Akurasi Passing Pada Futsal MAN 1 Tangerang Selatan - Foggy Abed Al Billal; Andri Irawan; Bambang Kridasuwarso (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to determine, 1) increasing Passing accuracy through the Rondos training method, 2) increasing Passing accuracy using the Circle Passing Drill training method, 3) the difference in increasing Passing accuracy using the Rondos training method and Circle Passing Drill. This research method uses an experimental method with research using a two groups